Comparative Kurdish Politics in the Middle East
XVIII, 235 p. 1 illus.
Keywords: This edited volume introduces the political, social and economic intra-Kurdish dynamics in the Middle East by comparatively analyzing the main actors, their ideas, and political interests. As an ethnic group and a nation in the making, Kurds are not homogeneous and united but rather the Kurdish Middle East is home to various competing political groups, leaderships, ideologies, and interests. Although many existing studies focus on the Kurds and their relations with the nation-states that they populate, few studies analyze the Kurdish Middle East within its own debates, conflicts and interests from a comparative perspective across Iran, Iraq, Turkey, and Syria. This book analyzes the intra-Kurdish dynamics with historically-grounded, theoretically-informed, and conceptually-relevant scholarship that prioritizes comparative politics over international relations. .